Marvels of Cosmos: Philosophico Theological Appraisal Based on Science Linguistics and Anthropology - Lameswar Kanhor; KANHOR (Lameswar) (New Delhi Christian World Imprints, 2014)
The Book deals with the Mathematical Zero and its Philosophical applications, Quantum Reality and Big Bang Cosmology, Quantum Zero and the Origin of the Universe, Philosophic Theological appraisal of the Nothingness, based on linguistic, numerical, physical and inner nothingness along with a general critique and evaluation of the whole study.
Keywords: Philosophy; Philosophical Theology; Religion and Science; Quantum Cosmology; Numerals--Religious aspects--Christianity; Anthropological Linguistics; Big bang theory